Pengaruh Penambahan Fe dan Al-5TiB Terhadap Fluiditas, Kekerasan, dan Struktur Mikro Paduan Al-7Si - Ikhsan Pujadany; Is Prima Nanda; Tengku Jukdin Saktisahdan (TIN: Terapan Informatika Nusantara, 2026)
The development of the automotive industry has become a strategic sector in the national economy, especially after the COVID-19 pandemic. To remain competitive, the automotive industry must continuously find new methods to improve product quality, such as in aluminum alloys which are widely used in vehicles. However, the use of secondary aluminum alloys is still common, and one of the main challenges in producing automotive components from these secondary alloys is controlling casting defects such as porosity, cracks, and non-uniform microstructures defects that are generally caused by iron (Fe) content and imperfect casting processes. This study aims to evaluate the effects of variations in experimental Fe content (1.2-1.8%) and the addition of the Al-5TiB grain refiner (0.45%) to an Al-7Si alloy on fluidity, hardness, and microstructure. The results show that the alloy treated only with Al-5TiB produced the highest fluidity (106.5 cm). Addition of Fe at the lower portion of the experimental range (1.2-1.4%) drastically reduced fluidity to 53-57.5 cm, whereas at the middle portion of the range (1.6-1.8%) fluidity recovered to 86-98.5 cm. The optimal combination Fe 1.6% with Al-5TiB 0.45% yielded a fluidity of 92.3 cm together with a synergistic hardness averaging 78.22 VHN. The best microstructure was achieved under these conditions, featuring equiaxed α-Al grains sized 26-40 µm, well-defined grain boundaries (<0.5 µm), and a dispersion of intermetallic particles (Fe₂AlB₂, AlTi) as well as TiB₂ crystallites of ~24 nm, which enhance surface strengthening without compromising flowability.